Haematopoietic Cell Transplantation with and without Sorafenib Maintenance for Patients with FLT3-ITD Acute Myeloid Leukaemia in first complete remission - Brunner, Andrew M. (Br J Haematol, 2016)
We performed a retrospective study analysing the effect of sorafenib, an oral fms-Like Tyrosine Kinase 3 (FLT3/multikinase inhibitor, as post-transplant maintenance in adult patients with FLT3-internal tandem duplication (ITD) acute myeloid leukaemia (AML). We identified consecutive patients with FLT3-ITD AML diagnosed between 2008 and 2014 who received haematopoietic cell transplantation (HCT) in first complete remission (CR1). Post-HCT initiation of sorafenib (yes/no) was evaluated as a time-varying covariate in the overall survival/progression-free survival (OS/PFS) analysis and performed a landmark analysis of controls alive without relapse at the median date of sorafenib initiation. We identified 26 sorafenib patients and 55 controls. Median follow-up was 27.2 months post-HCT for sorafenib survivors, and 38.4 months for controls (p=0.021). The median time to initiating sorafenib was 68 days post-HCT; 43 controls were alive without relapse at this cut-off. Sorafenib patients had improved 2-year OS in the d+68 landmark analysis (81% vs. 62%, p=0.029). Sorafenib was associated with improved 2-year PFS (82% vs. 53%, p=0.0081) and lower 2-year cumulative incidence of relapse (8.2% vs. 37.7%, p=0.0077). In multivariate analysis, sorafenib significantly improved OS (Hazard ratio [HR] 0.26, p=0.021) and PFS (HR 0.25, p=0.016). There was no difference in 2-year non-relapse mortality (9.8% vs. 9.3%, p=0.82) or 1-year chronic graft-versus-host disease (55.5% vs. 37.2%, p=0.28). These findings suggest potential benefit of post-HCT sorafenib in FLT3-ITD AML, and support further evaluation of post-HCT FLT3 inhibition.